PENGARUH MOTIVASI, PERSEPSI DAN PERTIMBANGAN PASAR KERJA TERHADAP MINAT MAHASISWA AKUNTANSI PPAK DALAM PEMILIHAN KARIR SEBAGAI AKUNTAN PUBLIK (Study Empiris pada Universitas PPAK di Sumatra) - Mega Diana Sari; Amir Hasan; Elfi Ilham (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
This study aimed to determine the effect of motivation, perception and labor market considerations to interest accounting students in the selection of a public accounting career. This research was conducted by using descriptive method survey. Collecting data in this study are primary data obtained from questionnaires distributed directly to the respondents. Sample selection technique is purposive sampling. The sample used in this study were 100 respondents who consisting of 20 accounting students of PPAK Program each of Riau University in Pekanbaru, Sumatra Utara University in Medan, Andalas University in Padang,  Sriwijaya University in Palembang, and Lampung University in Lampung. Management and analysis of data using multiple  linear regression analysis with the help of software SPSS version 20 (Statistical Product and Service Solution). The result shows that motivation, perception and labor market considerations have a significant influence on interest accounting students in the selection of a public accounting career.   Keywords: Motivation, Perception, Interest, career, and Public accounting.